Prejudice against homosexuals in Indonesia’s heteronormative cultural context: The roles of cultural humility and right-wing authoritarianism - Natalia Purnomo; Marselius Sampe Tondok (Jurnal Psikologi Tabularasa, 2025)
In Indonesia, heteronormative values remain widely upheld, contributing to persistent prejudice against homosexual individuals. Factors influencing such prejudice include cultural humility and right-wing authoritarianism. This study aims to examine the roles of cultural humility and rightwing authoritarianism in predicting prejudice against homosexuals. Employing a cross-sectional survey design, the study recruited a sample of heterosexual university students (N = 408) aged 18–25. Data were collected using standardized scales and analyzed through multiple regression. The findings indicate that cultural humility is negatively associated with prejudice (b = -0.23;p < 0.001), whereas right-wing authoritarianism is positively associated (b = 0.74; p < 0.001). Right-wing authoritarianism, which frames homosexuals as a societal threat, emerged as a stronger predictor of prejudice than cultural humility. Additional analyses revealed associations between prejudice and factors such as religious affiliation, faculty type, university type, and acquaintance with homosexual individuals. These results suggest that interventions aimed at reducing prejudice should prioritize addressing right-wing authoritarian attitudes, while also fostering cultural humility as a complementary strategy.